2020
DOI: 10.1108/bfj-06-2019-0414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of utilitarian and hedonic values on consumer willingness to buy and to pay for organic olive oil in Tunisia

Abstract: PurposeThis paper aims to study the influence of organic food perceived values (utilitarian vs hedonic) on consumer willingness to buy and willingness to pay in a developing country.Design/methodology/approachThis paper utilized a survey of 467 Tunisian consumers of organic olive oil. Data were analyzed using structural equation modeling (SEM) to test the reliability and validities of constructs, as wells as model fit and the structural model.FindingsThe findings indicate that both utilitarian and hedonic valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 45 publications
8
41
0
1
Order By: Relevance
“…In terms of organic food, these values can be derived from the greater level of freshness inherent in the product, the better taste and the feelings of consumers that they are doing a good thing both for the environment and their own health (Petljak et al , 2017). Other researchers have confirmed that experience confers a sense among consumers that they are doing the right thing, as well as enjoying products that are fresh and untainted by chemicals (Anastasiou et al , 2017; Ghali, 2020; Lee and Yun, 2015). Ghazali et al (2017) added that the hedonic value of a product is a major factor in driving the purchasing patterns of consumers.…”
Section: Utilitarian and Hedonic Values Of Organic Food And Purchase Intentionmentioning
confidence: 93%
See 3 more Smart Citations
“…In terms of organic food, these values can be derived from the greater level of freshness inherent in the product, the better taste and the feelings of consumers that they are doing a good thing both for the environment and their own health (Petljak et al , 2017). Other researchers have confirmed that experience confers a sense among consumers that they are doing the right thing, as well as enjoying products that are fresh and untainted by chemicals (Anastasiou et al , 2017; Ghali, 2020; Lee and Yun, 2015). Ghazali et al (2017) added that the hedonic value of a product is a major factor in driving the purchasing patterns of consumers.…”
Section: Utilitarian and Hedonic Values Of Organic Food And Purchase Intentionmentioning
confidence: 93%
“…Consequently, the greater the perception of the value of organic produce, the greater the likelihood of intention or affective behaviour in regard to buying this produce (Chen, 2010; Tsai et al , 2012). Ghali (2020) stated in that organic produce can instigate both hedonic and utilitarian values. These values can therefore to be said to drive consumers' behaviours and can guide their decision whether to buy such goods (Nejati and Moghaddam, 2013).…”
Section: Utilitarian and Hedonic Values Of Organic Food And Purchase Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hedonic approach has been applied in many research areas to measure consumer's willingness to pay for the products. For example, Ghali (2020) applied structural equation modeling to explore the influence of organic food perceived values (utilitarian vs. hedonic) on consumer willingness to buy and willingness to pay for organic oil in a developing country and found that both utilitarian and hedonic values have significant influence on consumer willingness to buy and to pay for organic olive oil. Nepal, Rai, Khadayat, and Somanathan (2020) used hedonic pricing model to analyze the characteristics that affect consumer purchasing decisions on house units in Nepal based on sub‐sample of nationally representative household survey data from urban areas as well as primary data collected from one of the metropolitan cities.…”
Section: Literature Reviewmentioning
confidence: 99%